2012
DOI: 10.1002/ajpa.22054
|View full text |Cite
|
Sign up to set email alerts
|

Brief communication: Short‐ and long‐term in vivo human buccal–dental microwear turnover

Abstract: Buccal-dental microwear depends on the abrasive content of chewed foodstuffs and can reveal long-term dietary trends in human populations. However, in vivo experimental analyses of buccal microwear formation processes are scarce. Here, we report the effects of an abrasive diet on microwear rates in two adult volunteers at intervals of 8 days over a period of 1 month and document long-term turnover over 5 consecutive years in the same subjects under an ad libitum Mediterranean diet. Buccal microwear was analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
89
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(97 citation statements)
references
References 31 publications
1
89
0
2
Order By: Relevance
“…In addition, forceful tooth-to-tooth contact and dental grinding are non-dietary sources of microwear features (both pits and scratches) on occlusal surfaces [45,47]. In contrast, buccal microwear is not affected by occlusal wear and dentine exposure [48] and has been shown to have a clearly distinct in vivo feature formation dynamics, and is likely to have a longer formation span than occlusal surfaces [49–51]. Buccal microwear is the result of the interaction of abrasive particles, such as plant phytoliths or silica dust, with the buccal enamel surfaces of teeth during chewing [52,53], as food particles move around in the mouth (mainly in an up-to-down and front-to-back direction) until they are swallowed.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, forceful tooth-to-tooth contact and dental grinding are non-dietary sources of microwear features (both pits and scratches) on occlusal surfaces [45,47]. In contrast, buccal microwear is not affected by occlusal wear and dentine exposure [48] and has been shown to have a clearly distinct in vivo feature formation dynamics, and is likely to have a longer formation span than occlusal surfaces [49–51]. Buccal microwear is the result of the interaction of abrasive particles, such as plant phytoliths or silica dust, with the buccal enamel surfaces of teeth during chewing [52,53], as food particles move around in the mouth (mainly in an up-to-down and front-to-back direction) until they are swallowed.…”
Section: Introductionmentioning
confidence: 99%
“…Grit may be the primary factor in the production of dental microwear (Sanson et al 2007;Lucas et al 2013). Experimental studies have shown that microwear forms when siliceous grit comes into contact with the teeth (Romero et al, 2012). In addition, Galbany et al (2014) and Romero et al (2012) proposed that the production of enamel microwear is dependent on particle size.…”
Section: Dietary Reconstruction Of P Robustusmentioning
confidence: 98%
“…Experimental studies have shown that microwear forms when siliceous grit comes into contact with the teeth (Romero et al, 2012). In addition, Galbany et al (2014) and Romero et al (2012) proposed that the production of enamel microwear is dependent on particle size. For example, large particles are more likely to fracture the enamel surface, whereas small particles produce indentations.…”
Section: Dietary Reconstruction Of P Robustusmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, recent research of the observed long-term stability of buccal microwear patterns has shown them to be a reliable indicator of overall dietary habits (Romero et al 2012).…”
Section: Introductionmentioning
confidence: 99%